RELIGIOUS HARMONY HANDLING IN WEST ACEH, INDONESIA - Sudarman, Sudarman; Ramadhani, Ayu (Jurnal Public Policy, 2018)
The purpose of this study is to provide an overview of interfaith communities’ existence in West Aceh until 2018 look’s harmonious without any disputes and conflicts. Although regarding Christians worship houses establishing had been hindered, because of the regulation that specifically regulates about the worship houses establishment according to the Aceh Qanun No. 4/2016 concerning guidelines for maintaining religious harmony and the workship places establishment, more interesting to study about the situation of religious harmony and social vulnerability in West Aceh District. This study uses a qualitative data analysis through the descriptive analysis approach and involved 5 informants that selected using purposive sampling i.e. government elements, the Religion’s Management Ministry, administrators of the Religious Harmony Forum (FKUB) and religious leaders. The results showed that the religious harmony control in West Aceh was under FKUB with a management administrator’s that involved interfaith leaders. The social vulnerability begins when the workship places establisment rules are limited by the Qanun with special conditions in order to the non-Muslim peoples must worship together clandestinely. The role limited of non-Muslim peoples in FKUB because of minority factor is perceived as a discrimination form, next step of non-Muslim peoples starting to strengthen themselves with the addition of community number Keywords: Religious Harmony, Social, Vulnerable, ConflictThe purpose of this study is to provide an overview of interfaith communities’ existence in West Aceh until 2018 look’s harmonious without any disputes and conflicts. Although regarding Christiansworship housesestablishing had been hindered, because of the regulation that specifically regulates about the worship houses establishment according to the Aceh Qanun No. 4/2016 concerning guidelines for maintaining religious harmony and the workship places establishment, more interesting to study about the situation of religious harmony and social vulnerability in West Aceh District. This study uses a qualitative data analysis through the descriptive analysis approach andinvolved 5 informants that selected using purposive sampling i.e. government elements, the Religion’s Management Ministry, administrators of the Religious Harmony Forum (FKUB) and religious leaders. The results showed that the religious harmony control in West Aceh was under FKUB with a management administrator’s that involved interfaith leaders. The social vulnerability begins when the workship places establisment rules are limited by the Qanun with special conditions in order to the non-Muslim peoples must worship together clandestinely. The role limited of non-Muslim peoples in FKUB because of minority factor is perceived as a discrimination form, next step of non-Muslim peoples starting to strengthen themselves with the addition of community number.